Кинематический и динамический анализ колесно-шагающей машины на основе компьютерных моделей в пакетах ADAMS и VisualNastran - Журавков, М. А.; Гляков, С. А.; Громыко, А. О.; Громыко, О. В. (БНТУ, 2008)
Paper deal with computer simulation of the wheel-stepping machine (WSM) using VisualNastran and ADAMS programs facilities. WSM motion process, trajectories, turnability parametres were calculated for different transference modes and situations.